How Does Adult Attachment Affect Human Recognition of Love-related and Sex-related Stimuli: An ERP Study - Hou, Juan; Chen, Xin; Liu, Jinqun; Yao, Fangshu; Huang, Jiani; Ndasauka, Yamikani; Ma, Ru; Zhang, Yuting; Lan, Jing; Liu, Lu; Fang, Xiaoyi (Frontiers in Psychology, 2016)
In the present study, we investigated the relationship among three emotion-motivation systems (adult attachment, romantic love and sex). We recorded Event-related potentials (ERPs) in 37 healthy volunteers who had experienced romantic love while they viewed SEX, LOVE, FRIEND, SPORT and NEUTRAL images. We also measured adult attachment styles, level of passionate love and sexual attitudes. As expected, results showed that, firstly, response to love-related image-stimuli and sex-related image-stimuli on the electrophysiological data significantly different on N1, N2 and PSW components. Secondly, the different adult attachment styles affected individuals’ recognition processing in response to love-related and sex-related images, especially, to sex-related images. Further analysis showed that voltages elicited by fearful attachment style individuals were significantly lower than voltages elicited by secure and dismissing attachment style individuals on sex-related images at frontal sites, on N1 and N2 components. Thirdly, from behavior data, we found that adult attachment styles were not significantly related to any dimension of sexual attitudes but were significantly related to passionate love scale total points. Thus, the behavior results were not in line with the electrophysiological results. The present study proved that adult attachment styles might mediate individuals’ lust and attraction systems.